Snus use in football: the threat of a new addiction? - Daniel Read; Sarah Carter; Phil Hopley; Karim Chamari; Lee Taylor (Biology of Sport, 2023)
The use of Snus, an oral nicotine pouch, is becoming increasingly common in English professional football. As a nicotine product, Snus raises important questions about health and performance for practitioners. The purpose of this short communication is to explain the current regulatory status of Snus, performance relatedeffects, and associated health outcomes. Further, based on player statements and evidence from the general public, we argue that Snus is used as a coping mechanism to deal with the stressors of professional football. Accordingly, the communication concludes with guidance for club-level multidisciplinary interventions to support player welfare, aimed at reducing Snus use as well as future research recommendations.